Prevalence and architecture of posttranscriptionally impaired synonymous mutations in 8, 320 genomes across 22 cancer types. Issue 3 (17th January 2020) - Teng, Huajing; Wei, Wenqing; Li, Qinglan; Xue, Meiying; Shi, Xiaohui; Li, Xianfeng; Mao, Fengbiao; Sun, Zhongsheng
Abstract: Somatic synonymous mutations are one of the most frequent genetic variants occurring in the coding region of cancer genomes, while their contributions to cancer development remain largely unknown. To assess whether synonymous mutations involved in post-transcriptional regulation contribute to the genetic etiology of cancers, we collected whole exome data from 8, 320 patients across 22 cancer types. By employing our developed algorithm, PIVar, we identified a total of 22, 948 posttranscriptionally impaired synonymous SNVs (pisSNVs) spanning 2, 042 genes. In addition, 35 RNA binding proteins impacted by these identified pisSNVs were significantly enriched. Remarkably, we discovered markedly elevated ratio of somatic pisSNVs across all 22 cancer types, and a high pisSNV ratio was associated with worse patient survival in five cancer types. Intriguing, several well-established cancer genes, including PTEN, RB1 and PIK3CA, appeared to contribute to tumorigenesis at both protein function and posttranscriptional regulation levels, whereas some pisSNV-hosted genes, including UBR4, EP400 and INTS1, exerted their function during carcinogenesis mainly via posttranscriptional mechanisms. Moreover, we predicted three drugs associated with two pisSNVs, and numerous compounds associated with expression signature of pisSNV-hosted genes. Our study reveals the prevalence and clinical relevance of pisSNVs in cancers, and emphasizes the importance of considering posttranscriptional impaired synonymous mutations in cancer biology.